1996
DOI: 10.1002/(sici)1098-2337(1996)22:5<375::aid-ab6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Fallow deer tactic to compete over food with red deer

Abstract: Small ungulates may compete with larger species through higher mobility, greater aggressiveness, and/or by larger group sizes. We observed a herd of approximately 100 red deer (Cervus elaphus) and 130 fallow deer (Dama dama) at the Žehušice Deer Park during supplemental feeding to determine whether fallow deer can displace red deer at feeding sites and to describe strategies used for displacement. Data were analyzed during the antlered period (AP) when males of both species had hard antlers and the cast period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Although the effects of supplementary feeding on the community ecology of ungulates is poorly understood, increased fallow deer densities are likely to increase competitive pressures on other ungulate species, including the moose, particularly during spring and summer when species overlap in their resource use. Moreover, from studies elsewhere in Europe, fallow deer is known to displace other species from feeding sites, such as roe deer (Ferretti et al 2008) and red deer (Bartoš et al 1996).…”
Section: Implications For Ungulate Health and Competitive Interactionmentioning
confidence: 99%
“…Although the effects of supplementary feeding on the community ecology of ungulates is poorly understood, increased fallow deer densities are likely to increase competitive pressures on other ungulate species, including the moose, particularly during spring and summer when species overlap in their resource use. Moreover, from studies elsewhere in Europe, fallow deer is known to displace other species from feeding sites, such as roe deer (Ferretti et al 2008) and red deer (Bartoš et al 1996).…”
Section: Implications For Ungulate Health and Competitive Interactionmentioning
confidence: 99%
“…Fallow bucks at feeding stations in a deer park in Germany were observed to be aggressive to red stags and hinds (Bartos et al 1996) and aggression has been reported between calving red deer and mule deer in Colorado (Stephens et al 2003). However, in a behavioural study considering interactions between introduced white-tailed deer (Odocoileus virginianus), long-established fallow deer and native red and roe deer in the Czech Republic (Bartos et al 2002), interspecific agonistic interactions were rarely observed.…”
Section: Interference Competitionmentioning
confidence: 99%
“…In captivity, the fallow deer has been reported to be intolerant of the red deer (Bartoš et al 1996) and of the spotted deer Axis axis (McGhee and Baccus 2006).…”
Section: Introductionmentioning
confidence: 95%